2010
DOI: 10.1503/cmaj.100461
|View full text |Cite
|
Sign up to set email alerts
|

Management of patients with acute hyperkalemia

Abstract: A 72-year-old man presents to his family physician for follow-up of hypertension, reporting fatigue and generalized weakness. His medical history also includes peptic ulcer disease, type 2 diabetes mellitus and chronic kidney disease. The estimated glomerular filtration rate is 30 mL/min per 1.73 m 2 . His medications include metformin, lansoprazole, acetylsalicylic acid, hydrochlorothiazide and ramipril, the dose of which was increased two weeks earlier to address suboptimal blood pressure control. Blood work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 30 publications
1
58
0
5
Order By: Relevance
“…Therefore, it is advisable that serum K + be maintained within the normal range (3.5-5.0 mEq/L) among patients with CKD. For hypokalemia, management is reasonably straightforward because most patients can be corrected with oral supplements (13). Clinicians should be particularly vigilant in monitoring for hypokalemia, a potent precipitant in the setting of diuretic use, as this and other studies have shown (14).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is advisable that serum K + be maintained within the normal range (3.5-5.0 mEq/L) among patients with CKD. For hypokalemia, management is reasonably straightforward because most patients can be corrected with oral supplements (13). Clinicians should be particularly vigilant in monitoring for hypokalemia, a potent precipitant in the setting of diuretic use, as this and other studies have shown (14).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperkalemia should be monitored closely and treated with insulin, glucose and calcium gluconate, 4 as per established protocols. 20 Hemodialysis should be considered for refractory hyperkalemia, especially in the setting of oliguria. The rapid accumulation of potassium in the setting of oliguria and the potential for hypocalcemia from the hyperphosphatemia are two reasons why a lower threshold for starting dialysis in these patients has been suggested.…”
Section: Preventionmentioning
confidence: 99%
“…Hyperkalemic patients presenting with evidence of cardiac instability should receive rapid therapy to stabilize the myocardium according to the standard of care (eg, intravenous calcium chloride or gluconate). 32 Dialysis may also be considered for the treatment of acute hyperkalemia. 32 Acute therapy is recommended when serum potassium is >6.5 mmol/L or when cardiac manifestations of hyperkalemia are present regardless of the serum potassium concentration.…”
Section: Practical Clinical Management Of Hyperkalemia Acute Hyperkalmentioning
confidence: 99%
“…32 Dialysis may also be considered for the treatment of acute hyperkalemia. 32 Acute therapy is recommended when serum potassium is >6.5 mmol/L or when cardiac manifestations of hyperkalemia are present regardless of the serum potassium concentration. 33 However, it is important to recognize that the ECG can be normal, even with severe hyperkalemia.…”
Section: Practical Clinical Management Of Hyperkalemia Acute Hyperkalmentioning
confidence: 99%